Pengayaan Arang Sekam Menggunakan Fermentasi Pupuk Organik Cair pada Pertumbuhan Balangeran (Shorea balangeran (Kroth.)) - Reni Rahmawati; Chartina Pidjath; Raudah Raudah (HUTAN TROPIKA, 2023)
This study combined peat soil and rice husk charcoal which had been soaked using liquid organic fertilizer fermented grass and eggs as a planting medium to reduce the acidity of peat soils so as to improve the physical properties of the soil and reduce the use of inorganic fertilizers while maintaining plant productivity. The purpose of this study was to analyze the growth of Balangeran tillers (Shorea balangeran) in combination with peat and husk charcoal planting media which had been enriched by liquid organic fertilizer fermented grass and eggs at different doses and types of treatment. This study used a randomized block design (RBD) calculation method with four treatments consisting of three groups and each group consisted of 10 S. balangeran puppies or 120 seadlings. The results of observations on the height parameter showed that P1 (husk charcoal + 10% egg fermentation) showed the best plant height with an average value of 7.47 cm, P3 treatment (husk charcoal + 5% egg fermentation + 5% grass fermentation) showed the best stem diameter. with an average value of 1.66 mm, P1 (charcoal husk + 10% egg fermentation) showed the best number of leaves with an average value of 3.23 leaves.